2005
DOI: 10.1080/00016480510044214
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception in elderly patients following cochlear implantation

Abstract: The surgical procedure was well tolerated by all patients without notable perioperative complications. In terms of speech perception, no significant differences between the elderly patients and younger recipients were noted. All patients found that cochlear implantation had a positive impact on their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 13 publications
3
35
1
Order By: Relevance
“…Cochlear implantation carries minimal risk and has been proven to be a safe procedure in all age groups (Venail et al, 2008) including the older population (Budenz et al, 2011;Carlson et al, 2010;Chatelin et al, 2004;Coelho, Yeh, Kim, & Lalwani, 2009;Djalilian, King, Smith, & Levine, 2002;Eshraghi et al, 2009;Haensel, Ilgner, Chen, Thuerman, & Westhofen, 2005;Labadie, Carrasco, Gilmer, & Pillsbury, 2000;Orabi, Mawman, Al-Zoubi, Saeed, & Ramsden, 2006). These authors generally agree that older adults present with more comorbid conditions at the time of surgery, and the patient's preexisting medical conditions are more important for determining intra-or postoperative complications than age alone.…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 81%
See 2 more Smart Citations
“…Cochlear implantation carries minimal risk and has been proven to be a safe procedure in all age groups (Venail et al, 2008) including the older population (Budenz et al, 2011;Carlson et al, 2010;Chatelin et al, 2004;Coelho, Yeh, Kim, & Lalwani, 2009;Djalilian, King, Smith, & Levine, 2002;Eshraghi et al, 2009;Haensel, Ilgner, Chen, Thuerman, & Westhofen, 2005;Labadie, Carrasco, Gilmer, & Pillsbury, 2000;Orabi, Mawman, Al-Zoubi, Saeed, & Ramsden, 2006). These authors generally agree that older adults present with more comorbid conditions at the time of surgery, and the patient's preexisting medical conditions are more important for determining intra-or postoperative complications than age alone.…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 81%
“…These authors generally agree that older adults present with more comorbid conditions at the time of surgery, and the patient's preexisting medical conditions are more important for determining intra-or postoperative complications than age alone. The outcomes of implantation in older adults are excellent such that speech understanding is significantly improved between preoperative and postoperative test intervals (Djalilian et al, 2002;Eshraghi et al, 2009;Haensel et al, 2005;Labadie et al, 2000;Migirov, Taitelbaum-Swead, Drendel, Hildesheimer, & Kronenberg, 2010;Orabi et al, 2006;Pasanisi et al, 2003;Shin et al, 2000). The benefits of improved audibility and speech recognition are expected to cascade into other areas of life such as the patient's social, psychological, and overall physical health.…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 90%
See 1 more Smart Citation
“…However, studies have consistently shown that older adults do, in fact, receive considerable benefits from CI, specifically in terms of speech perception, without significant differences in complications [Budenz et al, 2011;Haensel et al, 2005;Kelsall et al, 1995;Labadie et al, 2000;Orabi et al, 2006;Shin et al, 2000;Vermeire et al, 2005]. Some studies have shown that speech perception performance may be poorer than in younger adults [Budenz et al, 2011;Chatelin et al, 2004], but others have shown no difference between age groups [Haensel et al, 2005;Shin et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…22 Since elderly patients perform equally well as younger CI recipients, age is not a barrier to device insertion. 23 At present there are three major manufacturers of CIs, including Cochlear Corporation, Advanced Bionics Corporation and Med-El Corporation.…”
Section: Cochlear Implantsmentioning
confidence: 99%